2014
DOI: 10.1080/01924036.2014.973049
|View full text |Cite
|
Sign up to set email alerts
|

Insiders and outsiders: social change, deviant others, and sense of community in a boomtown

Abstract: In the last decade, the city of Fort McMurray, Alberta has undergone significant social changes due to the rapid growth of the oilsands industry in and around the city. In this short period of time, Fort Murray's population has more than doubled attracting migrants from all over Canada and internationally to fill labor shortages in the city. In the process, Fort McMurray has become a twenty-first century boomtown. Drawing on in-depth interviews, this article examines how young people and (adult) key informants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…A recent case study conducted by Genareo and Filteau () on an unidentified school district in North Dakota revealed that local residents tend to attribute social disruptions and risks to newcomers. A similar conclusion was also drawn by O'Connor () on the city of Fort McMurray, Alberta, Canada.…”
Section: Energy Boom and Crimessupporting
confidence: 82%
“…A recent case study conducted by Genareo and Filteau () on an unidentified school district in North Dakota revealed that local residents tend to attribute social disruptions and risks to newcomers. A similar conclusion was also drawn by O'Connor () on the city of Fort McMurray, Alberta, Canada.…”
Section: Energy Boom and Crimessupporting
confidence: 82%
“…Further, population growth, not only in energy boomtowns, can lead to perceptions of increased crime (Brown, 2011;Kennedy & Krahn, 1984). Studies in energy growth communities outside of the Bakken oil play have also focused on how residents perceive crime and disorder (O'Connor, 2015;Ruddell & Ortiz, 2014). Ruddell and Ortiz (2014) found that more residents of a boomtown thought that crime had increased in their community than respondents to a general survey of Canadians, and that their worries about crime decreased along with actual crime rates over the study period.…”
Section: Crime and Perceptions Of Crime In Oil And Gas Boomtownsmentioning
confidence: 99%
“…Much of this work, for example, has examined the social dislocation of rapid growth and development and the tensions between newcomers and longer term residents, and/or the strains on local social institutions (Freudenburg et al . ; Jacquet and Stedman ; O'Connor ; Stockdale ). Other work has more closely examined boomtown development from a longitudinal perspective, looking at social and economic impacts across the boom‐bust cycle, as rapid economic expansion gives way to production slowdowns and industrial scale backs once the resource has been depleted or extraction and development is otherwise no longer feasible (see, e.g., Shelton et al .…”
Section: Introductionmentioning
confidence: 99%